2011
DOI: 10.5012/bkcs.2011.32.3.905
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic Study of the Ã1A" - X~1A' System of CHBr

Abstract: We report fluorescence excitation and emission spectra of the CHBr molecule generated via pyrolysis of CH3Br in a molecular beam experiment. The 193 nm attenuation cross sections were estimated from the reduction of the CHBr signal as a function of the excimer laser fluence. The derived 193 nm absorption cross section for CHBr [(3.24 ± 0.59 ], but the difference is within the estimated uncertainties in the measured cross section.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Due to the numerous interactions between the electronic states, such as Renner–Teller effect, spin–orbit coupling, avoided crossing, or nonadiabatic interaction leading to predissociation, the spectroscopy and photodissociation dynamics of halocarbenes are rather complicated, which stimulate scientists to continuously perform experimental and theoretical studies on these important reactive intermediates. During past several decades, with the advances of high-resolution laser-based spectroscopic techniques along with theoretical methods, a variety of halocarbenes, including monohalogenated carbenes CHF /CHCl /CHBr /CHI, dihalogenated carbenes CCl 2 , CBr 2 , CFCl, CFBr, and CFI, and so on, have been widely investigated by using, for example, rotational-resolved laser absorption, laser-induced fluorescence (LIF), optical–optical-double-resonance (OODR), and stimulated emission pumping (SEP) techniques, as well as ab initio calculations. The structure, spectroscopy, and interactions of the ground state and the lowest singlet/triplet excited states of the halocarbenes have been studied comprehensively. Although sparse studies concerning higher excited states have emerged, for example, photodissociation dynamics of CHF and CDF at the B state, CCl 2 at 248 nm , and 193 nm, and CHCl, CFCl, and CFBr at 193 nm …”
Section: Introductionmentioning
confidence: 99%
“…Due to the numerous interactions between the electronic states, such as Renner–Teller effect, spin–orbit coupling, avoided crossing, or nonadiabatic interaction leading to predissociation, the spectroscopy and photodissociation dynamics of halocarbenes are rather complicated, which stimulate scientists to continuously perform experimental and theoretical studies on these important reactive intermediates. During past several decades, with the advances of high-resolution laser-based spectroscopic techniques along with theoretical methods, a variety of halocarbenes, including monohalogenated carbenes CHF /CHCl /CHBr /CHI, dihalogenated carbenes CCl 2 , CBr 2 , CFCl, CFBr, and CFI, and so on, have been widely investigated by using, for example, rotational-resolved laser absorption, laser-induced fluorescence (LIF), optical–optical-double-resonance (OODR), and stimulated emission pumping (SEP) techniques, as well as ab initio calculations. The structure, spectroscopy, and interactions of the ground state and the lowest singlet/triplet excited states of the halocarbenes have been studied comprehensively. Although sparse studies concerning higher excited states have emerged, for example, photodissociation dynamics of CHF and CDF at the B state, CCl 2 at 248 nm , and 193 nm, and CHCl, CFCl, and CFBr at 193 nm …”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that 4 1 A′ is a bent state, confirming the prediction of Shin and Park et al that CHBr is initially excited to a nonlinear excited state after absorbing 193 nm photons. 38…”
Section: Resultsmentioning
confidence: 99%
“…Hall et al 37 investigated the visible spectrum of CHBr, indicating the perturbation of parallel sub-bands being attributed to the predicted higher-energy excited state B 1 A′′. Shin and Park et al 38 reported the spectrum of CHBr produced by the pyrolysis of CH 3 Br using fluorescence excitation and emission spectroscopy. The researchers speculated that the CHBr molecule was excited to a nonlinear highly excited state after absorbing a 193 nm-laser photon, but the electronic states involved in the dissociation process and the corresponding photodissociation dynamics remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Dissociation resulting in a loss of Br is particularly relevant to atmospheric ozone chemistry as the Br atom is much more destructive to ozone than the other halogen atoms including the Cl atom. Bromine-containing halocarbons especially these bromine-substituted carbenes are the important subject of the experimental and theoretical studies in recent decades. Herein, we focus on CBr 2 carbene.…”
Section: Introductionmentioning
confidence: 99%